Parameter estimation of magnetic growing rod with output error method - YILDIRIM, ALPER (My University, 2023)
This study focuses on a magnetic controlled growing rods (MCGR) used in the treatment of early-onset scoliosis. In this study, the Lyapunov direct method-based output error method, which is iterative adaptive by online, is used as a parameter estimation method to predict the velocity of the telescopic bar during the MCGR distraction process. The system parameters are estimated. by the proposed model. The main purpose is to minimize the error between the actual and desired states by the online configuration of the controller’s parameters. By using online models, we can continuously update and refine system parameters to improve prediction accuracy.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Kontrol Sistemleri ve Enstrümantasyon; Uyarlanır Sistemler; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Control and System Engineering; Control Systems and Instrumentation; Adaptive Systems; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; OTOMASYON & KONTROL SİSTEMLERİ; TELEKOMÜNİKASYON; Engineering, Computing & Technology (ENG); ENGINEERING; AUTOMATION & CONTROL SYSTEMS; TELECOMMUNICATIONS; Kontrol ve Optimizasyon; Bilgisayar Ağları ve İletişim; Fizik Bilimleri; Control and Optimization; Control and Systems Engineering; Computer Networks and Communications; Physical Sciences